Diazepam Protects Against the Enhanced Toxicity of Cocaine Adulterated With Atropine - Daniela Braida; Alessia Zani; Valeria Capurro; Giuseppe Rossoni; Simona Pegorini; Enzo Gori; Mariaelvina Sala (Elsevier, 2008)
We examined the toxicity of cocatropine (cocaine/atropine mixture) and the therapeutic potential of diazepam on some behavioral and physiological parameters in rats. Atropine (20 and 60 mg/kg) or cocaine (40 mg/kg) alone did not induce any seizure or death, but the combination significantly increased both, after both acute and binge treatment. There was a significant increase of EEG mean total spectral power in cocatropine- in comparison with cocaine-treated animals. Hyperlocomotion was observed in non-seizuring rats treated with cocaine or cocatropine. Cocaine, atropine 60, and cocatropine (40 + 20 and 40 + 60) all induced hyperthermic effects in non-seizuring rats, while cocatropine (40 + 60)-seizuring animals had hypothermia. An initial hypertensive and tachycardiac effect within 15 min was followed by a secondary fall in the cocatropine (40 + 60) group. Cocatropine toxicity was partially or fully reversed by diazepam (5 mg/kg), given intraperitoneally after the first seizure. The present findings provide, for the first time, details of a synergistic toxic effect of the cocaine/atropine mixture and of the potential of diazepam for treating cocatropine-related hospital emergencies. Keywords:: drug abuse, crystalline, anticholinergic, binge, behavior